1986
DOI: 10.1002/jsfa.2740370303
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose accumulation and osmotic potentials in sugar beet at increasing levels of potassium nutrition

Abstract: In a pot experiment sugar beet Beta vulgaris L. ssp. vulgaris, cv. Kawetina, was grown on alluvial soil (21 mg exchangeable K 100 g−1) containing 0 (K1), 20 (K2), 40 (K3) and 60mg fertiliser K 100 g−1 soil (K4). The plants were sown on 15 March 1983 and harvested on 23 June, 14 July and 30 August 1983. At final harvest root dry weight/plant had reached 269 g in K1 and between 304 and 310 g in K2‐K4. Sucrose values were 15% (K1) and 17.3–17.7% of root fresh weight (K2‐K4) respectively. The osmotic potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 10 publications
2
16
0
2
Order By: Relevance
“…During beet growth, non‐sucrose vacuolar osmotica such as potassium and sodium are progressively replaced by sucrose 35. This is emphasized by the negative correlation between the concentrations of sucrose and the measured inorganic ions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…During beet growth, non‐sucrose vacuolar osmotica such as potassium and sodium are progressively replaced by sucrose 35. This is emphasized by the negative correlation between the concentrations of sucrose and the measured inorganic ions.…”
Section: Discussionsupporting
confidence: 86%
“…Betaine is a cytosolic osmoticum that has been detected in several plant species, reaching especially high concentrations in sugar beet 37. Beringer et al 35 measured a significant correlation between sucrose and betaine concentrations in sugar beet grown under controlled conditions. They concluded that increasing sucrose concentration in the vacuoles gives rise to higher non‐sucrose solute concentration in the cytosol to balance the osmotic potential within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in our experiment in the case of sucrose in all leaves of sugar beet plants that was also demonstrated but to a lesser extent in beet mature leaves by Mäck and Hoffman (2006). Beringer et al (1986) and Kenter and Hoffman (2005) showed that there was a strong positive correlation between concentrations of sucrose and glycine betaine in sugar beet storage roots. As a response to a low precipitation the concentration of both solutes in the tap-roots of sugar beet plants was increased but by different magnitude, only 5% for sucrose and 57% for betaine as compared with wellwatered plants (Mäck and Hoffman 2006).…”
Section: Resultssupporting
confidence: 64%
“…Glycine betaine (GB) N,N,N-trimethyl-glycine is an amino acid derivative naturally synthesized and accumulated in response to variety of abiotic stress conditions by numerous organisms including bacteria, cyanobacteria, algae, fungi, animals and in plant families [1]. Highest amount of GB is present in storage roots of sugar beet in epicotyl and hypocotyl tissues [2]. GB is one of the most studied compatible compound for abiotic stress tolerance due to its versatile function.…”
Section: Introductionmentioning
confidence: 99%